2020
DOI: 10.1101/2020.04.20.052118
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adherens junction serves to generate cryptic lamellipodia required for collective migration of epithelial cells

Abstract: Collective migration of epithelial cells plays crucial roles in various biological processes such as cancer invasion. In migrating epithelial sheets, leader cells form lamellipodia to advance, and follower cells also form similar motile apparatus at cell-cell boundaries, which are called cryptic lamellipodia (c-lamellipodia). Using adenocarcinoma-derived epithelial cells, we investigated how c-lamellipodia are generated, and found that they sporadically grew from Ecadherin-based adherens junctions (AJs). WAVE … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…It has been suggested that cortical contractility may operate for single cells, whereas lamellipodia may be involved where larger cells, or small groups of cells, are being extruded [ 29 ]. These mechanisms are not necessarily exclusive, as cryptic lamellipodia which extend underneath migrating epithelial cells can also form AJ [ 36 , 37 ].…”
Section: Apoptotic Cell Extrusionmentioning
confidence: 99%
“…It has been suggested that cortical contractility may operate for single cells, whereas lamellipodia may be involved where larger cells, or small groups of cells, are being extruded [ 29 ]. These mechanisms are not necessarily exclusive, as cryptic lamellipodia which extend underneath migrating epithelial cells can also form AJ [ 36 , 37 ].…”
Section: Apoptotic Cell Extrusionmentioning
confidence: 99%
“…Scale bars: 1 µm. (c) Comparison of optical sectioned images of human colon carcinoma (Caco2) cells expressing Lifeact-red fluorescent protein (RFP) visualizing actin filaments [21], collected by wide-field, TIRF microscopy (TIRFM), and lattice light-sheet microscopy (LLSM) (left column). In wide-field and TIRFM, the same field of view was imaged using a TIRFM system (Nikon).…”
Section: Principles Of Llsmmentioning
confidence: 99%